The Regional Skåne SOM Survey 2006 - SOM Institute, University of Gothenburg (University of Gothenburg, 2008)
This is the third SOM survey carried out in the Skåne region. Like Southern SOM 2004, the 2006 survey was carried out in the whole Skåne region. The questionnaire consists of nine coherent parts: news and daily papers; politics and society; society and service; media and society; holdings of technology and internet; traffic; activities and leisure habits; working life; and background.

Purpose:

Study attitudes and behaviour linked to local and regional issues

Detta är den tredje SOM-undersökning som genomförts i Skåne. Liksom Syd-SOM 2004 har Syd-SOM 2006 genomförts i hela region Skåne. Frågeformuläret består av nio sammanhållna frågeområden: nyheter och dagstidningar; politik och samhälle; samhälle och service; medier och samhälle; teknikinnehav och Internet; trafik; aktiviter och fritidsvanor; arbetsliv; samt bakgrundsfrågor.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
SOM-undersökningen i Skåne 2006
Syd-SOM 2006
Keywords: population migration; migration; immigrants; invandrare; internal politics; inrikespolitik; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap